ATRIP Deacetylation by SIRT2 Drives ATR Checkpoint Activation by Promoting Binding to RPA-ssDNA - Hui Zhang; PamelaSara E. Head; Waaqo Daddacha; Seong-Hoon Park; Xingzhe Li; Yunfeng Pan; Matthew Z. Madden; Duc M. Duong; Maohua Xie; Bing Yu; Matthew D. Warren; Elaine A. Liu; et al. (Cell Reports, 2016)
The ataxia telangiectasia-mutated and Rad3-related (ATR) kinase checkpoint pathway maintains genome integrity; however, the role of the sirtuin 2 (SIRT2) acetylome in regulating this pathway is not clear. We found that deacetylation of ATR-interacting protein (ATRIP), a regulatory partner of ATR, by SIRT2 potentiates the ATR checkpoint. SIRT2 interacts with and deacetylates ATRIP at lysine 32 (K32) in response to replication stress. SIRT2 deacetylation of ATRIP at K32 drives ATR autophosphorylation and signaling and facilitates DNA replication fork progression and recovery of stalled replication forks. K32 deacetylation by SIRT2 further promotes ATRIP accumulation to DNA damage sites and binding to replication protein A-coated single-stranded DNA (RPA-ssDNA). Collectively, these results support a model in which ATRIP deacetylation by SIRT2 promotes ATR-ATRIP binding to RPA-ssDNA to drive ATR activation and thus facilitate recovery from replication stress, outlining a mechanism by which the ATR checkpoint is regulated by SIRT2 through deacetylation.